The Effect of Exercise Intensity on Total PYY and GLP-1 in Healthy Females: A Pilot Study - Jillian R. Hallworth; Jennifer L. Copeland; Jon Doan; Tom J. Hazell (Journal of Nutrition and Metabolism)
We compared the acute response of anorexigenic signals (total PYY and GLP-1) in response to submaximal and supramaximal exercise. Nine females completed three sessions: (1) moderate-intensity continuous training (MICT; 30 min; 65%  VO2max); (2) sprint interval training (SIT; 6 × 30 sec “all-out” cycling sprints with 4 min recovery); or (3) control (CTRL; no exercise). PYY and GLP-1 were measured via blood samples drawn before, immediately after, and 90 min after exercise. Perceptions of hunger were rated using a visual analogue scale at all blood sampling time points. There was a session × time interaction for GLP-1 (p=0.004) where SIT and MICT (p<0.015 and p<0.001) were higher compared to CTRL both immediately and 90 min after exercise. There was a main effect of time for PYY where 90 min after exercise it was decreased versus before and immediately after exercise. There was a session × time interaction for hunger with lower ratings following SIT versus MICT (p=0.027) and CTRL (p=0.031) 90 min after exercise. These results suggest that though GLP-1 is elevated after exercise in women, it is not affected by exercise intensity though hunger was lower 90 min after exercise with SIT. As the sample size is small further study is needed to confirm these findings.